Effects of quinamic acid on cadmium distribution and excretion in mice and rats - Yan Xue-Ming; Tao Zheng-Qin; Liang You-Yi; Chen Zhen-Jia; Zhang Jian-Shi; Xu Xin-Hua (Acta Pharmacologica Sinica, 2016)
Quinamic acid, bis(3-carboxy-5-N-dicarboxymethylaminomethyl-6,7- dihydroxy-1,2,3,4-tetrahydroisoquinolinyl-8)-5,8-dimethyl-6,7-dihydroxy-l,2,3,4- tetrahydroisoquinoline-3-carboxylie acid, is a new polyaminocarboxylic acids chelating agent. It was first synthesized in this institute. Quinamic acid ip 500 mg/kg after iv 109CdCl2 in mice, reduced the cadmium contents in the liver and the brain (p